Advanced Glycation End Product Accumulation Is Associated With Low Skeletal Muscle Mass, Weak Muscle Strength, and Reduced Bone Density: The Nagahama Study. (11th October 2018) - Tabara, Yasuharu; Ikezoe, Tome; Yamanaka, Mikihiro; Setoh, Kazuya; Segawa, Hiroaki; Kawaguchi, Takahisa; Kosugi, Shinji; Nakayama, Takeo; Ichihashi, Noriaki; Tsuboyama, Tadao; Matsuda, Fumihiko; ,
Abstract: Background: The accumulation of advanced glycation end product (AGE) might exert deleterious effects on musculoskeletal properties. Our study aims to clarify this possible association in a large general population. Methods: This study investigated a general population of 9, 203 patients (mean age, 57.8 years). Skeletal muscle mass was measured by bioelectrical impedance analysis, whereas accumulation of AGEs was assessed by skin autofluorescence (SAF-AGE). The muscle strength of upper and lower limbs and usual gait speed were measured in a portion of older (≥60 years of age) participants ( n = 1, 934). The speed of sound (SOS) in the calcaneal bone was assessed via a quantitative ultrasound technique. Results: In the total population, the frequency of low skeletal muscle mass linearly increased with the SAF-AGE quartiles (Q1: 14.2%, Q2: 16.1%, Q3: 21.1%, Q4: 24.8%; p < .001), and this association was independent of covariates including glycemic traits (Q4: odds ratio [OR] = 1.48, p < .001). The association between the highest SAF-AGE quartile and low skeletal muscle mass remained significant in the older subpopulation (OR = 1.85, p = .002). A similar but weak association was observed for low SOS (Q1: 8.9%, Q2: 8.3%, Q3: 10.4%, Q4: 12.2%; p < .001). Similar inverse associations were also observed with grip strength (OR = 1.98, p = .003), hip flexion strength (OR = 1.50, p = .012), and hip abduction strength (OR = 1.78, p = .001), but not with usual gait speed. Conclusion: Accumulation of AGEs might be a deleterious factor for musculoskeletal properties.